2021
DOI: 10.1016/j.atmosres.2021.105681
|View full text |Cite
|
Sign up to set email alerts
|

Impact of horizontal resolution on monsoon precipitation for CORDEX-South Asia: A regional earth system model assessment

Abstract: For the first time for CORDEX-South Asia, a high-resolution regional earth system model (ROM) is adopted to assess the impact of horizontal resolution (0.22 • and 0.11 • ) in simulating the Indian summer monsoon rainfall (ISMR) and the underlying spatiotemporal variability. ROM at both resolutions bears a close resemblance to observations in simulating the mean precipitation climatology compared to other regional climate models (RCMs) participated in CORDEX-South Asia. ROM shows substantial improvement relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…From the figure, it can be noticed that the model shows a slightly different pattern of relationship during all decades. The misrepresentation of the ISMR-IOD relationship is one of the possible causes of model limitation in simulating the ISMR (overestimation over southwest-central India) reported in the earlier study of this model (Mishra et al, 2021a(Mishra et al, , 2021b. Most of the ISMR related studies have reported the limited skill of the model to reproduce ISMR correctly.…”
Section: Physical Mechanism Associated With Iodmentioning
confidence: 84%
See 1 more Smart Citation
“…From the figure, it can be noticed that the model shows a slightly different pattern of relationship during all decades. The misrepresentation of the ISMR-IOD relationship is one of the possible causes of model limitation in simulating the ISMR (overestimation over southwest-central India) reported in the earlier study of this model (Mishra et al, 2021a(Mishra et al, , 2021b. Most of the ISMR related studies have reported the limited skill of the model to reproduce ISMR correctly.…”
Section: Physical Mechanism Associated With Iodmentioning
confidence: 84%
“…1). A detailed description of the model setup can be found in Sein et al (2015Sein et al ( , 2020 and (Mishra et al, 2021b).…”
Section: Model Setupmentioning
confidence: 99%
“…However, it is computationally expensive, and alternatively, high-resolution RESM can be used at a less computational cost. Various RESM having varying complexities have been developed and employed to explore the understanding of atmospheric and oceanic variability over different regions of the globe and suggest improvements (Sein et al, 2015;Wang et al, 2015;Dubey et al, 2021;Mishra et al, 2021aMishra et al, , 2021bSaharwardi et al, 2021;Kumar et al, 2022;Mishra et al, 2022aMishra et al, , 2022bMishra et al, , 2022c. Kumar et al (2022) demonstrated that dynamical and thermodynamical processes including the upper tropospheric circulation associated with the Indian summer monsoon employing the same model used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is computationally expensive, and alternatively, high‐resolution RESM can be used at a less computational cost. Various RESM having varying complexities have been developed and employed to explore the understanding of atmospheric and oceanic variability over different regions of the globe and suggest improvements (Sein et al ., 2015; Wang et al ., 2015; Dubey et al ., 2021; Mishra et al ., 2021a, 2021b; Saharwardi et al ., 2021; Kumar et al ., 2022; Mishra et al ., 2022a, 2022b, 2022c). Kumar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the global climate models participating in CMIP5 activities have a nominal resolution of about 150 km in the atmosphere and 1° in the ocean (Eyring et al., 2016; T. Rackow et al., 2018; Taylor et al., 2012) providing a reasonable trade‐off between computing time and model complexity. Various studies noted the improvement in the model performance (either global or regional) by increasing the atmospheric or oceanic resolution over most parts of the world (Bador et al., 2020; de la Vara et al., 2020; Güttler et al., 2015; Hack et al., 2006; Mishra et al., 2021; Moreno‐Chamarro et al., 2022; Strandberg & Lind, 2021; Tsartsali et al., 2022). Strandberg and Lind (2021) show notable improvement in high or moderate precipitation intensities over Europe after increasing atmospheric resolution (downscaling CMIP5 with a regional climate model).…”
Section: Introductionmentioning
confidence: 99%